2009
DOI: 10.1007/s12540-009-0409-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ammonia producing Bacillus sp. on corrosion of cupronickel alloy 90:10

Abstract: The objective of the present investigation is characterization of ammonia producing bacteria (Bacillus sp.) and its impact on biodeterioration of cupronickel alloy 90:10. It is well known that iron sulphate and molybdenum are good inhibitors used in cooling water system. The role of interaction between inhibitor and ammonia producing bacteria on corrosion of cupronickel 90:10 was studied. Cupronickel coupons were immersed in Chavara rare earth containing backwater for a period of six months. The predominated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…It should also be kept in mind that the crystallization of calcium oxalate leads to a decrease in the content of oxalate ions in the medium and may lead to an increase in pH. An increase in pH is often observed also in aging cultures of microorganisms and may be a consequence of the release of nitrogen metabolism products by bacteria, as well as the formation of lysis products of aging cells [5,39,40]. Since the pH increases with time, it can be concluded that the influence of factors contributing to the increase in pH (in particular, the products of nitrogen metabolism) prevails in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be kept in mind that the crystallization of calcium oxalate leads to a decrease in the content of oxalate ions in the medium and may lead to an increase in pH. An increase in pH is often observed also in aging cultures of microorganisms and may be a consequence of the release of nitrogen metabolism products by bacteria, as well as the formation of lysis products of aging cells [5,39,40]. Since the pH increases with time, it can be concluded that the influence of factors contributing to the increase in pH (in particular, the products of nitrogen metabolism) prevails in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Since the strains did not show high adhesive properties, they can be expected to participate in corrosion processes due to the influence of ammonium (a product of AMB metabolism), which is considered a corrosive compound (Maruthamuthu et al, 2009;Guo et al, 2022). IRB, similar to SRB, is capable of hydrogen consumption and electrode depolarization (De Windt et al, 2003;Hernández-Santana, 2021), destruction of mineral films of carbon steel surface due to iron-reducing activity, which increases the speed of corrosion processes (Valencia-Cantero & Pena-Cabriales, 2014).…”
Section: Biofilm Formation Of Heterotrophic Bacteria Isolated From So...mentioning
confidence: 99%